PENGARUH TINGKAT PENDIDIKAN, RELIGIUSITAS DAN PERAN RELAWAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA PEKANBARU TAMPAN - Ilham, Annisa Puteri; Suci, Rama Gita; Marlina, Evi (LPPM Universitas Putera Batam, 2025)
This study examines how the level of education, religiosity, and active role as a tax volunteer affect the compliance of individual taxpayers at KPP Pratama Pekanbaru Tampan. Using a quantitative approach, data is collected through observation, literature search, and distribution of questionnaires to taxpayers. Data analysis involves testing validity and reliability, as well as classical assumptions tests to ensure data quality. Multiple linear regression was used to measure the influence of each independent variable (education level, religiosity, role of tax volunteers) on taxpayer compliance. The sample size was determined by the Slovin formula, taking into account the number of taxpayers registered at KPP Pratama Pekanbaru Tampan as many as 400 people. The findings of the study indicate a positive and significant influence of the level of education, religiosity, and the role of tax volunteers on the level of compliance of individual taxpayers.